Determining the Level of Emotional Intelligence of Future Cynologists - Bilotserkovets, Marina; Fomenko, Tetiana; Pavlenko, Yuliia (Educational Challenges, 2024)
The purpose of the paper is to investigate the essence of emotional intelligence (EI) as an important component for future cynologists’ fruitful work in the sphere of rehabilitation of people who have been affected by the war consiquences. The authors studied the scientific literature on EI and its role in “Human-Human” and “Human-Animal” interactions in the working sphere. The authors determined the existing EI level of students who have Cynology as their major, outlined the theoretic and empiric outcomes, and stated recommendations for improving future cynologists’ professional training.Methodology. The empirical survey had a sample of 36 respondents. They were second-year students aged 18-21, 20 were male, and 16 were female. It was conducted by means of Google Forms on the basis of “Methodology of emotional intelligence diagnosis” by N. Hall (adapted) with subsequent processing and analysis of the results.Results. The study of the literature revealed that EI is of crucial importance for future cynologists’ professional fulfillment as it is responsible for the emotional regulation of their behavior, self-motivation, empathy, etc. However, empirically, it was found out that the EI of the respondents had not been sufficiently developed, as 68% of the respondents had a low level of EI integrative index, 22% of the students had the medium level of EI integrative index. Solely 10% of the respondents were recorded to have a high-level EI integrative index.Conclusions. The outcomes of the study revealed that most respondents do not have sufficient EI development, but they have the potential to enhance it. The authors insist on the organization of special educational courses and training to develop the ability of future cynologists to understand their own emotions and the emotions of other people, emotional behavior management, self-motivation, etc.
Keywords: canistherapy; emotional intelligence; human-animal; human-human; professional training; war consequences